IMPLEMENTASI JASA MOBILE BRANCH DALAM MENINGKATKAN JUMLAH NASABAH - Sudianto Sudianto; Nur Fadilah; Bisyarotul Hanun (Al-Amien Prenduan for Islamic Institute, 2022)
Seeing the increasingly digital era, banks must pay attention to their information technology, so far Bank Muamalat KCP Sumenep has made innovations in serving customers. One of the innovations carried out by Bank Muamalat KCP Sumenep is in the form of a Mobile Branch. And utilizing information technology is a very appropriate solution in developing business and the services in it. This study uses a descriptive qualitative research method is a research that describes the type of research by observing the surrounding phenomena and analyzing these phenomena.The results of this study were obtained from interviews from the parties concerned, that the implementation of Mobile Branch services can increase the number of customers, but there are obstacles in it, namely the COVID 19 virus and the epidemic that hit the world, making all banks, especially Mobile Branches experience a decline. in developing its business and in increasing the number of customers. But in terms of Mobile Branch services provided to customers, they are also satisfied with their presence and services.